Epidemiology of spider mite sensitivity: a meta-analysis and systematic review - Zhou, Ying (Clin Transl Allergy, 2018)
BACKGROUND: Spider mites, including Tetranychus urticae, Panonychus citri, and Panonychus ulmi, are common pests in gardens, greenhouses, and orchards. Exposure, particularly occupational exposure, to these organisms may lead to the development of respiratory or contact allergies. However, the prevalence of sensitivity to spider mites is unclear. METHODS: We examined the literature to generate an estimate of the global prevalence of allergies to spider mites. RESULTS: Electronic databases were searched and twenty-three studies reporting the prevalence of sensitivity to spider mites (based on skin prick tests or IgE-based detection systems) in an aggregate total of 40,908 subjects were selected for analysis. The estimated overall rate of spider mite sensitivity was 22.9% (95% CI 19–26.8%). Heterogeneity was high and meta-regression analysis considering variables such as published year, country, number of study subjects, methods for allergen detection (skin prick test, ImmunoCAP, RAST testing, or intradermal test), and mite species revealed no single significant source. Twelve of the 23 studies reported rates of monosensitization (i.e., patients responsive to spider mites but no other tested allergen), yielding a global average of 7% (95% CI 5–9%), hence spider mites represent a unique source of allergens. CONCLUSIONS: Spider mites are an important cause of allergic symptoms. However, the publication bias and heterogeneity evident in this study indicate that further trials using standardized detection methods are needed to determine the association of exposure and symptoms as well as the specific patient characteristics that influence developing spider mite sensitivity.